Evaluation of systemic absorption of topical ophthalmic prednisolone acetate and dexamethasone in healthy dogs - Ewald, Margaret M. (Kansas State University, 2021)
Objective: To quantify plasma concentrations of prednisolone and dexamethasone following topical ophthalmic application of prednisolone acetate 1% and dexamethasone 0.1% to healthy adult dogs. Animals: 12 purpose-bred Beagles. Procedures: Dogs received one drop of either prednisolone acetate 1% (n=6) or neomycin polymyxin B dexamethasone (i.e., dexamethasone) 0.1% (n=6) ophthalmic suspension to both eyes every six hours for 14 days. Blood samples (peripheral and jugular) were collected on day 0, 1, 7, and 14 and analyzed by LC-MS for prednisolone and dexamethasone plasma concentrations. Plasma cortisol levels were measured at the beginning of the study (day 0) and at the end of topical drug administration (day 14). Results: Both drugs demonstrated systemic absorption. Prednisolone was detected (median; minimum – maximum) on days 1, 7, and 14 (24.80; 6.20 – 74 ng/mL), and dexamethasone was detected (median; minimum – maximum) on days 1, 7, and 14 (2.30; 0 – 17.70 ng/mL). Neither prednisolone nor dexamethasone were detected in plasma samples on day 0 (baseline). Sampling from the jugular vein resulted in higher plasma drug concentrations than peripheral venous samples when samples from each timepoint were combined. Plasma cortisol levels were significantly lower (P = 0.03) than baseline following 14 days of treatment with topical prednisolone acetate and dexamethasone. Conclusions and Clinical Relevance: Prednisolone and dexamethasone are detected in the plasma of healthy dogs following topical ophthalmic administration four times per day. Additional research is needed to evaluate the systemic absorption of topical ophthalmic prednisolone acetate and dexamethasone in dogs with ocular surface inflammation or anterior uveitis.
Keywords: Prednisolone acetate; Dexamethasone; Systemic absorption; Ophthalmic glucocorticoids